1997
DOI: 10.1002/(sici)1096-9861(19970908)385:4<641::aid-cne9>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopic demonstration of mGluR5 metabotropic glutamate receptor immunoreactive neuronal elements in the rat cerebellar cortex

Abstract: The cellular and subcellular localization of the mGluR5 metabotropic glutamate receptor subtype was studied in the rat cerebellar cortex, by using the preembedding immunoperoxidase and immunogold techniques. Light microscopic observations revealed an abundant, intense labeling of neurons in the granular layer as well as in the molecular layer. Lugaro and Golgi cells exhibited an intense mGluR5 immunoreactivity, while only a fraction of the neurons in the molecular layer were found to be mGluR5 immunopositive. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 33 publications
4
22
0
Order By: Relevance
“…mGluR1s inhibit GABAergic transmission at the synapses between molecular layer interneurons and Purkinje cells mGluR1 is the only group I mGluR isoform expressed in cerebellar Purkinje cells (Baude et al, 1993;Negyessy et al, 1997). On Purkinje cell dendrites, these receptors can be located in close apposition not only to glutamatergic terminals but also to GABAergic ones (Baude et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…mGluR1s inhibit GABAergic transmission at the synapses between molecular layer interneurons and Purkinje cells mGluR1 is the only group I mGluR isoform expressed in cerebellar Purkinje cells (Baude et al, 1993;Negyessy et al, 1997). On Purkinje cell dendrites, these receptors can be located in close apposition not only to glutamatergic terminals but also to GABAergic ones (Baude et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…DHPG induced three distinct events: (1) a transient inward current, which reflects the opening of cationic channels activated by mGluR1s in Purkinje cells (Batchelor et al, 1994;Tempia et al, 1998;Kim et al, 2003); (2) an increase of frequency of sIPSCs (Llano and Marty, 1995), likely through direct activation of mGluR1s and mGluR5s (Baude et al, 1993;Negyessy et al, 1997) on molecular layer interneurons; and (3) a marked decrease of the eIPSCs (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…A contribution of Ca 2ϩ release from inositol trisphosphate receptor (IP 3 R) activation to these signals or to their generation cannot be excluded. A possible induction mechanism for this pathway would be the activation of group I metabotropic glutamate receptors (mGluR), which could lead to IP 3 production (Berridge, 1998); however, mGluR1 and mGluR5 were not found in these axons at the adult stage (Baude et al, 1993;Negyessy et al, 1997), and a developmental study of mGluR1 distribution in Purkinje cells showed no evidence of these receptors at presynaptic structures from postnatal day 0 to adulthood (Lopez-Bendito et al, 2001). Intrinsic mechanisms, such as the state of Ca 2ϩ filling of the stores and spontaneous fluctuations in the intracellular Ca 2ϩ concentration, both of which will modulate IP 3 Rs and RyRs (Pozzan et al, 1994;Berridge, 1998), could be at the basis of SCaT generation.…”
Section: Discussionmentioning
confidence: 99%
“…In the brainstem, strong expression of mGlu5 has been detected in the shell regions of the inferior colliculus, superficial layers of the superior colliculus and caudal subnucleus of the spinal trigeminal nucleus. In the cerebellar cortex, only a small population (10%) of Golgi cells expresses mGlu5 and no expression has been detected in Purkinje cells or granule cells (Neki et al 1996a;Negyessy et al 1997). In the spinal cord, mGlu5 is strongly expressed in the superficial dorsal horn (Vidnyanszky et al 1994;Berthele et al 1999;Jia et al 1999).…”
Section: Distribution Of Group I Mglusmentioning
confidence: 99%